Analysis of Internal and External Factors Influencing Teacher Performance - Egi Dina Aulia; Burhanuddin Burhanuddin; Imron Arifin (Academia Open, 2025)
General Background: The quality of education fundamentally hinges on teacher performance, as educators are central to the learning process. Specific Background: Despite widespread acknowledgment of their significance, systemic efforts to enhance teacher effectiveness remain fragmented. Knowledge Gap: There is limited integrative analysis that systematically categorizes the full spectrum of internal and external factors influencing teacher performance. Aims: This study aims to identify and categorize the key determinants that shape teacher performance using descriptive analysis of empirical data. Results: Five primary factors emerged: personal characteristics, systemic structures, team collaboration, leadership, and contextual influences. Emotional stability was the most critical personal trait, while organizational systems and teamwork directly impacted task performance and student outcomes. Leadership supported ethical professionalism, and unaddressed contextual pressures risked performance decline. Novelty: The study’s novelty lies in its multidimensional synthesis of performance drivers, emphasizing the interplay between internal traits and external systems. Implications: Findings advocate for holistic educational policies that concurrently strengthen individual, structural, and contextual supports to sustainably elevate teaching quality. Highlights: Emotional stability is the most influential personal trait. School systems and teamwork enhance performance quality. Contextual pressure must be managed to avoid performance decline. Keywords: Teacher Performance, Educational Quality, Internal Factors, External Influences, School Leadership